2010
DOI: 10.3899/jrheum.090776
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Activity After 12 Weeks of Treatment with Nonbiologics in Early Rheumatoid Arthritis May Predict Articular Destruction 2 Years Later

Abstract: In patients with early RA, ACR core set measures after 12 weeks of nonbiologic DMARD treatment may predict articular destruction 2 years later. Low response to treatment at 12 weeks and continuing high disease activity thereafter were found in patients with rapid radiological progression. These data can be used to determine the appropriateness of treatment at 12 weeks and aid the decision to introduce biologic DMARD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
2
5
0
1
Order By: Relevance
“…Importantly, the addition of CZP to MTX inhibited radiographic progression in both the 12-week responder and nonresponder groups when compared with placebo. These results support the recent findings of Ichikawa, et al 25 , who found that in patients with early RA, ACR core set measures after 12 weeks of nonbiologic DMARD treatment predicted articular destruction 2 years later, demonstrating the importance of obtaining rapid control of disease activity in order to prevent longterm irreversible damage. Similarly, Smolen, et al demonstrated that attainment of remission or LDA at 3 months led to no or minimal progression of joint damage over a 1-year period in patients treated with MTX + infliximab 26 .…”
Section: Discussionsupporting
confidence: 91%
“…Importantly, the addition of CZP to MTX inhibited radiographic progression in both the 12-week responder and nonresponder groups when compared with placebo. These results support the recent findings of Ichikawa, et al 25 , who found that in patients with early RA, ACR core set measures after 12 weeks of nonbiologic DMARD treatment predicted articular destruction 2 years later, demonstrating the importance of obtaining rapid control of disease activity in order to prevent longterm irreversible damage. Similarly, Smolen, et al demonstrated that attainment of remission or LDA at 3 months led to no or minimal progression of joint damage over a 1-year period in patients treated with MTX + infliximab 26 .…”
Section: Discussionsupporting
confidence: 91%
“…Это соответствует материалам исследований других авторов, в которых было показано, что развитие ремиссии в течение первых 8-12 нед на фоне монотерапии МТ позволяет предсказать сохранение ремиссии через год. В то же время отсутствие ремиссии через 4-6 мес на фоне комбинированной терапии МТ и ГИБП ассоциируется с резистентностью к этой комбинации и свидетельствует о необходимости смены ГИБП [32][33][34][35][36][37].…”
Section: Discussionunclassified
“…[1][2][3][4][5] To our knowledge, this approach has not been utilized in patients with psoriasis receiving biologic therapies. Early improvements in disease activity have been associated with improved long-term clinical outcomes in psoriasis patients treated with methotrexate, as well as patients with other autoimmune diseases.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…Currently, there are no objective criteria for predicting responsiveness to biologic treatment for psoriasis. Early improvements in disease activity have been associated with improved long‐term clinical outcomes in psoriasis patients treated with methotrexate, as well as patients with other autoimmune diseases . To our knowledge, this approach has not been utilized in patients with psoriasis receiving biologic therapies.…”
mentioning
confidence: 99%